MiR‐646 regulates proliferation and migration of laryngeal carcinoma through the PI3K/AKT pathway via targeting GPX1. (26th November 2020) - Yuan, Xuanju; Liu, Yufeng; Chen, E.; Wang, Junhua; Deng, Shouping; Chen, Ping; Wang, Xianhe; Deng, Shouheng
Abstract: Laryngeal cancer is a common type of head and neck malignancy. microRNA is implicated in the development and progression of various tumours. The present study aimed to explore the potential roles and mechanisms of miR‐646 in laryngeal carcinoma cells. We detected the expression of miR‐646 and observed that miR‐646 was reduced in laryngeal cell lines. Subsequently, the proliferation, migration and invasion of TU212 and TU686 cells were evaluated using CCK‐8 assays, cell proliferation ELISA BrdU and transwell assays after transfection with miR‐646 mimic. Overexpression of miR‐646 attenuated the proliferative and invasive abilities of TU212 and TU686 cells. Dual luciferase reporter assay confirmed that glutathione peroxidase 1 (GPX1) is a direct target of miR‐646. Interestingly, restoration of GPX1 promoted cell proliferation and migration, and reversed the biological activities of miR‐646 in cell proliferation and migration. It is worth noting that miR‐646 overexpression blocked the activation of PI3K/AKT pathway, and this was partly abrogated by GPX1. 740Y‐P, a PI3K agonist abolished the effects of miR‐646 on cell proliferation and invasion. Taken together, miR‐646 prohibited the proliferation and invasion of laryngeal carcinoma cells through the PI3K/AKT pathway via targeting GPX1.